Do bipolar subjects' responses to personality questionnaires lack reliability? Evidence from the PsyCoLaus study. (30th April 2016) - Dupuis, Marc; Capel, Roland; Meier, Emanuele; Rudaz, Dominique; Strippoli, Marie-Pierre F.; Castelao, Enrique; Preisig, Martin; Vandeleur, Caroline L.
Abstract: Differences in personality scores between subjects with and without mood disorders might result from response biases rather than specific personality traits per se. The aim of this study was to compare subjects with bipolar disorders (BPD) to non-bipolar subjects in terms of response quality to the NEO-FFI. Using data from the population-based cohort study PsyCoLaus, subjects were compared in terms of responses to the NEO-FFI, and indices of response quality were calculated. Hierarchical regression analyses were performed and controlled for sociodemographic factors, depressive episodes, dysthymia, anxiety disorders and substance use disorders. Consistent with the literature, subjects with BPD had higher scores in neuroticism and openness, and lower scores in conscientiousness. However, significant differences were measured for response reliability and validity. In particular, the indices of response quality including response reliability were lower in subjects with BPD suggesting that bipolar subjects might have more difficulty in providing consistent answers throughout questionnaires. However, regression models resulted in small associations between mania/hypomania and response quality, and showed that differences in response quality were mainly attributable to correlates of BPD instead of the presence of mania/hypomania itself. The current findings suggest that bipolar subjects' responses to questionnaires are biased, making them less reliable. Highlights: The quality of self-ratings of personality was assessed for bipolar disorders. Bipolar and non-bipolar subjects were compared in terms of response quality. Lower indices of response reliability in particular were found among bipolars. Correlates of bipolar disorder were associated with lower response quality. Our findings question the use of self-rated questionnaires among bipolar subjects.